Planning and self-efficacy interventions encouraging replacing energy-dense foods intake with fruit and vegetable: A longitudinal experimental study. Issue 1 (2nd January 2016) - Luszczynska, Aleksandra; Horodyska, Karolina; Zarychta, Karolina; Liszewska, Natalia; Knoll, Nina; Scholz, Urte
Abstract : Objective : This longitudinal experimental study compared effects of self-efficacy, planning and education-based conditions, encouraging adolescents to eat fruit and vegetable in place of energy-dense foods. Design : Data were collected among 506 adolescents (13–18 years old) who were randomly assigned to control ( n = 181), planning ( n = 153) or self-efficacy ( n = 172) conditions. Measurements were taken at baseline (T1), at a 2-month follow-up (T2), and at a 14-month follow-up (T3). Interventions/control group procedures were delivered at T1 and T2. Outcome measures : Self-reports of fruit and vegetable intake (FVI) and energy-dense foods intake were collected at three times. Cognitive mediators (self-efficacy and planning) were assessed at T1 and T2. Body weight and height were objectively measured at T1 and T3. Results and conclusions : Similar significant increases of FVI were found for planning and self-efficacy interventions (T3). The planning intervention did not influence energy-dense food intake (T3), but the self-efficacy intervention tended to result in stabilising intake (compared to an increase found in the control group). There were no effects on body weight. Similar patterns were found for the total sample and for a subsample of adolescents with overweight/obesity. The effects of interventions on FVI were mediated by respective cognitions.